2002
DOI: 10.1034/j.1600-0420.2002.800303.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors in corneal wound healing following refractive surgery: A review

Abstract: ABSTRACT.The first part of this review article aims to provide important basic definitions of growth factor terminology, and to put forward a model for understanding the role of growth factors in a wound healing context. In the second part of the paper, we review the literature on growth factors in the cornea, including that on changes associated with wound healing following refractive surgery in the epithelial, stromal, and endothelial layers. The role of growth factors in stromal removal, corneal neovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 101 publications
1
85
0
3
Order By: Relevance
“…Several researchers have shown that growth factors such as EGF, TGF-β, bFGF, hepatocyte growth factor, PDGF, interleukin-6 and keratinocyte growth factor increase epithelial healing rates in vitro, but their in vivo effects after topical application are controversial (25). Some groups have reported that topical EGF application increased the wound-healing rate in vivo, but others reported no benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have shown that growth factors such as EGF, TGF-β, bFGF, hepatocyte growth factor, PDGF, interleukin-6 and keratinocyte growth factor increase epithelial healing rates in vitro, but their in vivo effects after topical application are controversial (25). Some groups have reported that topical EGF application increased the wound-healing rate in vivo, but others reported no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…After photorefractive keratectomy, the release of varying factors such as TGF-β, EGF, PDGF, vascular endothelial growth factor, hepatocyte growth factor and interleukin-6 has been reported. These growth factors have been further characterized by a recurrent set of events in a wound-healing context: injury-induced growth factor production and release, growth factor-induced proliferative and migratory re- sponses and morphologic changes in target cells, additional growth factor regulation through feedback loops and a specific termination process (25). Endogenous basic fibroblast growth factor (bFGF) levels, a member of the FGF family (26), have been shown to increase at injury sites (27).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical and/or surgical injury to the cornea triggers a wound healing response causing changes in extracellular matrix organization and cellular phenotype and density (Wilson et al, 2001;Jester et al, 1999a;Fini and Stramer, 2005). Numerous studies have shown that injury to the cornea facilitates release of multiple cytokines and growth factors from both corneal cells and the lacrimal glands (Fini, 1999;Mohan et al, 2003;Zieske, 2001;Baldwin and Marshall, 2002). Cytokines that have been shown to play important roles in maintaining corneal transparency and consequently clear vision are platelet-derived growth factor, transforming growth factor beta, fibroblast growth factor, and the interleukins (Jester et al, 1995;Jester et al, 2002;Girard et al, 1991;Masur et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of new tissue requires proliferation, migration, and differentiation of epithelial cells, which are stimulated by growth factors secreted by keratocytes, epithelial growth factor (EGF), keratinocyte growth factor, and hepatocyte growth factor (Klenkler and Sheardown, 2004;Wilson et al, 1994). The synthesis of new tissue also requires proliferation of the remaining keratocytes (Zieske, 2000) that are regulated by EGF, TGF-b, platelet-derived growth factor, and fibroblast growth factor, secreted by epithelial and inflammatory cells (Baldwin and Marshall, 2002) and the synthesis of a new extracellular matrix secreted by fibroblasts.…”
Section: Introductionmentioning
confidence: 99%